CORONAVIRUS IN THE REPUBLIC OF UZBEKISTAN DURING 2020-2023 RETROSPECTIVE EPIDEMIOLOGICAL ANALYSIS OF THE DISEASE ( TASHKENT CITY AS AN EXAMPLE) (World Bulletin of Public Health, 2024)
to evaluate the dynamics of formation and duration of maintenance of humoral immunity after administration of the 1st and 2nd doses of the BNT162b2 vaccine (Pfizer-BioNTech) in a group of children. Materials and methods. The research work used the results of the analysis of blood serum samples from 205 children in family clinics No. 16. Vaccine efficacy against SARS-CoV-2 was assessed in a retrospective population-based analysis using epidemiological, serological and statistical methods. Results: The results showed that IgM-Ab against SARS-CoV-2 was detected in 100% of cases on the 21st day after administration of the 1st component of the vaccine in the blood of vaccinated children (average positivity rate - 4.94), on the 30th day there was a natural decrease in the amount of IgM against SARS-CoV-2 (average positivity rate - 0. Conclusion: It is worth noting that on the 21st day of vaccination a significant decrease in IgM levels was detected, and on the 51st day these indicators leveled off. On the 21st day after vaccination with components 1 and 2, a direct positive correlation was revealed between the amount of IgM and IgG from 0.69 to 0.29 (r
Keywords: COVID-19; infection; prevention